Assessment of soil carbon dioxide efflux from contrasting land uses in a semi-arid savannah ecosystem, northeastern Ghana (West Africa) - Nat Owusu-Prempeh; Leonard K. Amekudzi; Boateng Kyereh (Scientific African)
Soil respiration (SR) emits a vast amount of atmospheric carbon dioxide (CO2) and contributes largely to the global greenhouse gas budget. The study assessed the dynamics of SR rates in the Vea catchment in northeastern Ghana, a sparsely gauged semi-arid savannah ecosystem characterized by distinct patterns of soil CO2 efflux. Through field measurements using soil chambers, the study quantified soil CO2 efflux rates in different land use types (woodland, cropland and grazeland), and assessed the influence of soil moisture, temperature, and soil organic carbon stocks on SR variability. The highest soil CO2 fluxes (12.97 ± 0.89 Mg CO2C ha−1 yr−1) were recorded in woodland, followed by grazeland (9.10 ± 0.42 Mg CO2C ha−1 yr−1) with cropland having the lowest rate (5.61 ± 0.29 Mg CO2C ha−1 yr−1). We recorded mean annual soil CO2 flux of 9.23 ± 0.53 Mg CO2C ha−1 yr−1 across the land use types and also observed significant seasonal and spatial variations in SR rates. The highest SR rate (220 mg CO2C m−2 h−1) was recorded in the wet months (Jul-Sept and Mar-May) and the lowest rate (30 mg CO2C m−2 h−1) in the dry months (Nov-Jan). For the wet season, the mean weekly soil CO2 fluxes ranged between 140 and 160 mg CO2C m−2 hr−1 as opposed to 60–75 mg CO2C m−2 hr−1 for the dry season. Seasonal and spatial variations in SR rates were largely driven by land use type, soil moisture and the interaction of soil temperature and moisture. The results underscore the importance of understanding the emission patterns from various land uses in West African savanna ecosystems to harnessing their potential for climate change mitigation.